Research Methodology for Analysis of E-Commerce User Activity Based on User Interest using Web Usage Mining - Saucha Diwandari; Adhistya Erna Permanasari; Indriana Hidayah (Journal of ICT Research and Applications, 2018)
Visitor interaction with e-commerce websites generates large amounts of clickstream data stored in web access logs. From a business standpoint, clickstream data can be used as a means of finding information on user interest. In this paper, the authors propose a method to find user interest in products offered on e-commerce websites based on web usage mining of clickstream data. In this study, user interest was investigated using the PIE approach coupled with clustering and classification techniques. The experimental results showed that the method is able to assist in analyzing visitor behavior and user interest in e-commerce products by identifying those products that prompt visitor interest.